Coronary Artery Dilation in Children with Febrile Exanthematous Illness without Criteria for Kawasaki Disease - Reyna,Jesus (2019)
Abstract Background: Coronary dilatation is the most important complication of Kawasaki disease (KD) and, in addition to some clinical characteristics, is common to KD and febrile exanthematous illnesses (FEIs). Objective: To assess whether children with FEI, who do not meet the criteria for KD, have changes in coronary arteries dimensions. Methods: Echocardiography was performed within the first two weeks of the disease in patients < 10 years with fever and exanthema without other KD criteria. To make a comparison with KD patients, we reviewed the echocardiograms and medical records of patients with a diagnosis of KD of the last five years. Coronary ectasia was assessed using Z scores of coronary arteries. The means of the dimensions of the coronary arteries were compared with a z test and a level of significance of 0.05 was adopted. Results: A total of 34 patients were included, 22 (64.7%) with FEI, and 12(35.2%) with a diagnosis of KD. Using the Z scores of coronary artery, a dilation of any of the coronary artery branches was observed in six (27.2%) patients with FEI. Conclusions: An important percentage of patients with FEI has coronary artery dilation.